2015
DOI: 10.1104/pp.114.253641
|View full text |Cite
|
Sign up to set email alerts
|

A Small Phospholipase A2-α from Castor Catalyzes the Removal of Hydroxy Fatty Acids from Phosphatidylcholine in Transgenic Arabidopsis Seeds  

Abstract: Ricinoleic acid, an industrially useful hydroxy fatty acid (HFA), only accumulates to high levels in the triacylglycerol fraction of castor (Ricinus communis) endosperm, even though it is synthesized on the membrane lipid phosphatidylcholine (PC) from an oleoyl ester. The acyl chains of PC undergo intense remodeling through the process of acyl editing. The identities of the proteins involved in this process, however, are unknown. A phospholipase A2 (PLA2) is thought to be involved in the acyl-editing process. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 58 publications
1
37
1
Order By: Relevance
“…For example, germination rates of fae1 RcFAH12 seeds show considerable variation, the exact mechanism of which is not clear. Lu et al (2006) observed a normal germination rate, whereas Bayon et al (2015) reported a 24% germination rate of fae1 RcFAH12 seeds. In our experiments, we observed germination rates from 30% to 98% between different batches of seeds.…”
Section: Discussionmentioning
confidence: 86%
“…For example, germination rates of fae1 RcFAH12 seeds show considerable variation, the exact mechanism of which is not clear. Lu et al (2006) observed a normal germination rate, whereas Bayon et al (2015) reported a 24% germination rate of fae1 RcFAH12 seeds. In our experiments, we observed germination rates from 30% to 98% between different batches of seeds.…”
Section: Discussionmentioning
confidence: 86%
“…<1.6‐fold), including the phospholipid acyl hydrolase genes PLA1 and PLA2 (Figure a,b), the non‐specific phospholipase C genes (Figure c) and summed expression for several phospholipase D, PLD , isoforms (Figure e). A castor bean PLA2 homologous to AT2G06925 in Arabidopsis was recently shown to reduce HFA accumulation in PC and TAG when expressed in Arabidopsis lines accumulating HFA (Bayon et al ., ). The Physaria homolog was only slightly more highly expressed (maximum 1.4‐fold) in Physaria than in Camelina, and the sequences were 91% identical compared to the mean identity of 89% across the eight Brassicaceae species (Figure i).…”
Section: Resultsmentioning
confidence: 97%
“…For example, variations in HFA content and oil quantity in the same genetic lines have been reported between different sets of experiments performed over a 10-year span (Adhikari et al, 2016;Bates et al, 2014;Bayon, Chen, Weselake, & Browse, 2015;Burgal et al, 2008;Lu et al, 2006;Lunn et al, 2018;van Erp et al, 2011van Erp et al, , 2015.…”
Section: Rcpdat1mentioning
confidence: 99%